(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2024)
The South African grade 10 history curriculum as outlined in the Curriculum and Assessment Policy Statement (CAPS) requires learners to develop historical thinking skills that promote interpretation, analysis, and critical thinking competencies. One way of developing these skills is through revisiting historical events through reenactments to explore untold stories and develop historical empathy. However, reenactments can become sensational, one-sided events that lack the transformative power to offer varied versions of the events such as the Battle at Egazini and its key historical figures. The paper proposes reenactment for learning as an interdisciplinary methodology that draws on art exhibitions, history literature, and applied theatre techniques. The paper shows how these teaching tools actively and creatively engaged the learner-audiences in the reenactment of the 1819 Battle at Egazini between the amaXhosa and the British in Makhanda, formerly Grahamstown. The facilitators moved learner-audiences from four local schools beyond passive reenactment modes of engagement using games, pantsula dancing, facilitator-in-role, enrolling participants, and reflection exercises in one-hour workshops. The activities helped learners explore the relevance of colonial expansion and conquest themes within the Battle at Egazini context. The art-based interpretation framework also helped address misconceptions and cultivated an interest in wanting to know more about Makhanda, the war hero that the town is now named after. The paper argues for a creative and engaging pedagogy that helps learners make sense of broad topics. It contributes to current literature advocating for creative historical interpretation and teaching approaches in and outside the classroom space.